2016
DOI: 10.1093/geront/gnw011
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Conditions in a Population-Based Sample of Older Homeless Adults

Abstract: Geriatric conditions were common among older homeless adults living in diverse environments, and the prevalence of these conditions was higher than that seen in housed adults 20 years older. Services that address geriatric conditions are needed for older homeless adults living across varied environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
172
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 115 publications
(181 citation statements)
references
References 46 publications
4
172
1
4
Order By: Relevance
“…3 The high prevalence of cognitive impairment in this population could be due to dementia, depression, or acute substance use. Their functional status is worse than those 20 years older in the general population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…3 The high prevalence of cognitive impairment in this population could be due to dementia, depression, or acute substance use. Their functional status is worse than those 20 years older in the general population.…”
Section: Discussionmentioning
confidence: 95%
“…2 Due to poor health, homeless adults are considered older at age 50. 3,4 Studies on older homeless populations show high rates of psychiatric morbidity, including depressive symptoms, psychiatric hospitalization, and alcohol use disorders. 5 Despite the high prevalence of mental health problems, there is limited research on predictors of psychiatric morbidity among older homeless adults.…”
Section: Introductionmentioning
confidence: 99%
“…Those born in the latter half of the baby boom (1954–1963) have had an elevated risk of homelessness throughout their lives (Culhane et al, 2013). For older homeless adults, chronic medical conditions, including geriatric syndromes, are causally linked to healthcare utilization and mortality (Brown et al, 2016b; Brown et al, 2012; Garibaldi et al, 2005; Gelberg et al, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…(7) A recent population-based study from homeless shelters in Oakland, California, has shown that homeless adults in their 50s have more geriatric conditions amenable to treatment than those two decades older who are stably housed. (8) It is evident that services that address geriatric conditions are needed for older homeless adults living across diverse environments such as homeless shelter or hotel, or those living transiently with family/friends.…”
Section: Introductionmentioning
confidence: 99%